2004
DOI: 10.1111/j.1600-0501.2004.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant design and intraosseous stability of immediately placed implants: a human cadaver study

Abstract: Immediately placed ITI TE implant leads to initial intraosseous stability and interface mechanical properties comparable with a wide diameter implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
107
4
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 22 publications
11
107
4
8
Order By: Relevance
“…This fixation is necessary for further osseointegration of the inserted surfaces of the implant with the surrounding bone [4]. Many factors may influence this process, including implant shape, diameter, length, angulation [5,6], surface treatment, bone quality, and surgical technique [7,8]. Lin et al found that the implant shape was an important determinant of stress distribution and has a more pronounced effect than implant length or diameter [9].…”
Section: Introductionmentioning
confidence: 99%
“…This fixation is necessary for further osseointegration of the inserted surfaces of the implant with the surrounding bone [4]. Many factors may influence this process, including implant shape, diameter, length, angulation [5,6], surface treatment, bone quality, and surgical technique [7,8]. Lin et al found that the implant shape was an important determinant of stress distribution and has a more pronounced effect than implant length or diameter [9].…”
Section: Introductionmentioning
confidence: 99%
“…After testing 276 immediate loaded implants using RFA, Balshi et al suggested that bone types II and III were more consistent in term of stability return, while bone types I and IV were not 19) . Primary stability, a function of bone quality, implant design, and surgical procedure, is one of the important factors that influences the survival rate of implants 17,20,27) . It has been reported that primary stability can serve as a useful predictor of osseointegration 16) .…”
Section: Discussionmentioning
confidence: 99%
“…The resonance frequency value thus obtained is converted to give an Implant Stability Quotient (ISQ) for analyzing implant stability [9][10][11][12] . Recently, this device has been used in implant research to perform the following tasks: compare the success rates between conventional and early loading of implants [13][14] , evaluate the survival rates of transmucosal implants immediately restored with single crowns 15) , monitor the differences between immediate and standard delayed loading of implants [16][17][18] , profile physiological and geometric factors affecting immediate loaded implants [19][20] , and measure stability achieved with one-stage surgical procedures [21][22] . However, clinical investigation has indicated that temporary attachment, removal, and sterilization of the transducer are time-consuming and far from being cost-effective 17) .…”
Section: Introductionmentioning
confidence: 99%
“…Higher bone density creates greater bone-implant contact and consequently, it increases the primary stability. On the other hand, a low bone density is associated to a higher implant failure rate 6,7 . Clinical studies shows that implants placed in the jaw present higher survival rates compared to the ones placed on the maxilla 8,9 , especially when considered the maxillary posterior region witch usually presents a thinner cortical bone combined with thicker trabecular bone 10 .…”
Section: Introductionmentioning
confidence: 99%